2022
DOI: 10.33594/000000573
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects Caused by Functionalized Carbon Nanotube in Murine Macrophages.

Abstract: BACKGROUND/AIMS: The development of new nanomaterials has been growing in recent decades to bring benefits in several areas, especially carbon-based nanoparticles, which have unique physical-chemical properties and allow to take on several applications. Consequently, the use of new nanomaterials without previous toxicological studies raises concern about possible harmful health effects. The aim of this study was to investigate the cytotoxic profile of a new multi-walled carbon nanotube (MWCNT) functionalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…This increase may be linked to the redox regulation that occurs in cells, that is, the balance between the formation and elimination of ROS, destroying the microenvironment, which can lead to cell death [ 32 , 33 ]. Our data corroborate those of Godoy et al, 2022 [ 21 ], who described an increase in ROS production at the highest concentrations of carbon nanotubes (ONCT-TEPA), in tests also performed on J774.A1 murine macrophages and murine fibroblasts [ 34 ]. The literature indicates that when ROS production is exacerbated and exceeds the limit of the cells’ antioxidant defense capacity, proteins and lipids are totally damaged, which can lead to a pathophysiological condition, an inflammatory process resulting in apoptosis [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This increase may be linked to the redox regulation that occurs in cells, that is, the balance between the formation and elimination of ROS, destroying the microenvironment, which can lead to cell death [ 32 , 33 ]. Our data corroborate those of Godoy et al, 2022 [ 21 ], who described an increase in ROS production at the highest concentrations of carbon nanotubes (ONCT-TEPA), in tests also performed on J774.A1 murine macrophages and murine fibroblasts [ 34 ]. The literature indicates that when ROS production is exacerbated and exceeds the limit of the cells’ antioxidant defense capacity, proteins and lipids are totally damaged, which can lead to a pathophysiological condition, an inflammatory process resulting in apoptosis [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…NP and protein corona interactions are crucial to this understanding, because these interactions are related to the mechanism by which NPs enter or do not enter cells. Protein corona formation causes NPs to lose their targeting ability and means that they can be easily phagocytosed by macrophages [ 21 ]. However, the direct relationships between cells and their resulting effects on NPs must be studied in detail [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond pristine CNMs in the above study, other research has compared the cytotoxicity of carboxylic acid-functionalized CNTs. One example of this is done by Aminzadeh et al, where they studied the reproductive toxicity of COOH-SWCNTs and COOH-MWCNTs in an in vitro setup on human spermatozoa. The results showed that neither CNTs had caused increased cell death at a concentration range of 0.1–100 μg/mL when incubated with sperms at 37 °C for 5 h as shown by the MTT test.…”
Section: Biomedical and Environmental Translation Of Cnmsmentioning
confidence: 99%